Effect of burner geometry on swirl stabilized methane/air flames: A joint LES/OH-PLIF/PIV study. (1st November 2017) - Liu, X.; Elbaz, A.M.; Gong, C.; Bai, X.S.; Zheng, H.T.; Roberts, W.L.
Abstract: Large eddy simulation (LES) using a transported PDF model and OH-PLIF/PIV experiments were carried out to investigate the quarl effects on the structures of swirl stabilized methane/air flames. Two different quarls were investigated, one straight cylindrical quarl and one diverging conical quarl. The experiments show that the flames are significantly different with the two quarls. With the straight cylindrical quarl a compact blue flame is observed while with the diverging conical quarl the flame appears to be long and yellow indicating a sooty flame structure. The PIV results show the formation of a stronger flow recirculation inside the diverging conical quarl than that in the straight quarl. LES results reveal further details of the flow and mixing process inside the quarl. The results show that with the diverging quarl vortex breakdown occurs much earlier towards the upstream of the quarl. As a result the fuel is convected into the air flow tube and a diffusion flame is stabilized inside the air flow tube upstream the quarl. With the straight quarl, vortex breakdown occurs at a downstream location in the quarl. The scalar dissipation rate in the shear layer of the fuel jet is high, which prevents the stabilization of a diffusion flame in the proximity of the fuel nozzle; instead, a compact partially premixed flame with two distinct heat release layers is stablized in a downstream region in the quarl, which allows for the fuel and air to mix in the quarl before combustion and a lower formation rate of soot. The results showed that the Eulerian Stochastic Fields transported PDF method can well predict the details of the swirl flame dynamics.